Pengaruh Pendidikan Pelatihan dan Fasilitas Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Papalang Kabupaten Mmauju - Lidiana, lidiana; Arifhan Ady DJ; Ahmad Karim; Anis Anshari Mas'ud; Harun; Dahliah (Jurnal Manarang Manajemen dan Bisnis, 2025)
This research aims to determine and analyze the influence of training education and work facilities on the performance of papalang district office employees Mamuju Regerency. The approach to this research is through approach quantitative, and this type oof research is survey, observation and interview. Location this research was carried out at the papalang district office located in the village Topore Majene-Mamuju Topore axis road, Papalang District, Regerency Mamuju, West Sulawesi. The population in this study were all employees there are 30 papalang sub-district offices in mamuju regerency employee. The sampling technique in this research is saturated sampling or census, where the entire population is used as a sample. Data analysis carried out using the likert scale method assisted by use SPSS version 26 program. The analysis results show that. 1.education has a positive and significant effect on employee performance. 2. Training have a positive and significant effect on employee performance. 3. Work facilities have a positive and significant effect on employee performance 4. Education, training and work facilities have a simultaneous effect on employee performance.